2017
DOI: 10.18632/oncotarget.14411
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Notch1 and Numb in small cell lung cancer

Abstract: Notch signaling in tumorigenesis functions as an oncogene or tumor suppressor according to the type of malignancy. Numb represses intracellular Notch signaling. Previous studies have demonstrated that Notch signaling suppresses the proliferation of small cell lung cancer (SCLC) cell lines. However, in SCLC, the association between Notch1 and Numb expression and clinicopathological factors or prognosis has remained unclear. In this study, we evaluated the expression of Notch1 and Numb in SCLC. We immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
(36 reference statements)
3
13
0
Order By: Relevance
“…In this study, we showed that nuclear NOTCH1 expression was negatively correlated with malignancy status, this means that loss of nuclear NOTCH1 expression, the presumably active protein, might favor neoplastic progression from precursor cervical lesions (CIN) to cancer (ICC). Similar findings were recently observed in a study of small cell lung cancer, in which high NOTCH1 expression was an independent favorable prognostic factor [ 45 ].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we showed that nuclear NOTCH1 expression was negatively correlated with malignancy status, this means that loss of nuclear NOTCH1 expression, the presumably active protein, might favor neoplastic progression from precursor cervical lesions (CIN) to cancer (ICC). Similar findings were recently observed in a study of small cell lung cancer, in which high NOTCH1 expression was an independent favorable prognostic factor [ 45 ].…”
Section: Discussionsupporting
confidence: 90%
“…Although DLL3 is a Notch ligand and ASCL1 is suppressed by Notch target genes , there were no correlations between DLL3 or ASCL1 expression with Notch1 expression using the tumor specimens from our previous study (supplemental online Fig. 1) . Moreover, we obtained data regarding the expression of neuroendocrine (NE)‐specific proteins, including chromogranin A, synaptophysin, and CD56, based on pathological reports of each surgical specimen when possible.…”
Section: Resultsmentioning
confidence: 99%
“…DLL3 and ASCL1 scoring was only assessed in histologically SCLC cells, not in cancer cells histologically characterized as squamous cell carcinoma, adenocarcinoma, or large cell carcinoma components. Notch1 protein expression from previously reported data was used for analysis .…”
Section: Methodsmentioning
confidence: 99%
“…IHC was performed as previous described [ 37 ]. Numb NICD1 and NICD4 were detected by IHC with a rabbit polyclonal anti-Numb antibody (1:500 dilution; ab14140, Abcam, Cambridge, UK) a rabbit monoclonal anti-NICD1 antibody (1:400 dilution; #3608, Cell Signaling, Danvers, MA, USA) and a rabbit polyclonal anti-NICD4 antibody (1:200 dilation; ab199295, Abcam, Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%